Social innovation in high-quality agricultural systems: metrics for assessing processes and outcomes - Santini Pigatto, Giuliana Aparecida; Brunori, Gianluca (Innovation: The European Journal of Social Science Research, 2021)
Social innovation and high-quality agricultural systems are important for rural development. However, there is little information on methods for measuring the process and outcome of social innovation, particularly at the regional level. This study aimed to answer the research question: Which social innovation metrics can be applied to analyze rural development at the regional level? We carried out a systematic review of the literature on factors and indicators of social innovation, assessed the characteristics of social innovation in value-added agricultural production systems in developed countries, and proposed social innovation indicators for evaluating value-added agricultural systems in developing countries. Key elements of the process and outcome dimensions of social innovation were identified and used to generate factors, subfactors, indicators, and subindicators. The literature review showed that more research is needed on the outcomes of social innovation. Future studies should investigate the social transformations promoted by rural tourism and biodiversity valorization.
Keywords: Agriculture; Développement rural; Europe; Innovation sociale; Mesure d'impact; Réservé UdeM; Transformations sociales

People centered social innovation: global perspectives on an emerging paradigm - Banerjee, Swati; Carney, Stephen; Hulgård, Lars (Routledge studies in social enterprise & social innovation, 2020)
People Centered Social Innovation: Global perspectives on an Emerging Paradigm attempts to revisit and extend the existing understanding of Social Innovation in practice by focusing upon the lived realities of marginalized groups and communities. The emerging field of people-centered development is placed in dialogue with theory and concepts from the more established field of social innovation to create a new approach; one that adopts a global perspective, engaging with very different experiences of marginality across the global north and south. Theoretically, ‘People Centered Social Innovation: Global Perspectives on an Emerging Paradigm’ draws upon ‘northern’ understandings of change and improvement as well as ‘southern’ theory concerns for epistemological diversity and meaning making. The result is an experiment aimed at reimagining research and practice that seriously needs to center the actor in processes of social transformation.
Keywords: Innovation sociale; Réservé UdeM; Transformations sociales

Social innovation in high-quality agricultural systems: metrics for assessing processes and outcomes - Santini Pigatto, Giuliana Aparecida; Brunori, Gianluca (Innovation: The European Journal of Social Science Research, 2021)
Social innovation and high-quality agricultural systems are important for rural development. However, there is little information on methods for measuring the process and outcome of social innovation, particularly at the regional level. This study aimed to answer the research question: Which social innovation metrics can be applied to analyze rural development at the regional level? We carried out a systematic review of the literature on factors and indicators of social innovation, assessed the characteristics of social innovation in value-added agricultural production systems in developed countries, and proposed social innovation indicators for evaluating value-added agricultural systems in developing countries. Key elements of the process and outcome dimensions of social innovation were identified and used to generate factors, subfactors, indicators, and subindicators. The literature review showed that more research is needed on the outcomes of social innovation. Future studies should investigate the social transformations promoted by rural tourism and biodiversity valorization.
Keywords: Agriculture; Développement rural; Europe; Innovation sociale; Mesure d'impact; Réservé UdeM; Transformations sociales

People centered social innovation: global perspectives on an emerging paradigm - Banerjee, Swati; Carney, Stephen; Hulgård, Lars (Routledge studies in social enterprise & social innovation, 2020)
People Centered Social Innovation: Global perspectives on an Emerging Paradigm attempts to revisit and extend the existing understanding of Social Innovation in practice by focusing upon the lived realities of marginalized groups and communities. The emerging field of people-centered development is placed in dialogue with theory and concepts from the more established field of social innovation to create a new approach; one that adopts a global perspective, engaging with very different experiences of marginality across the global north and south. Theoretically, ‘People Centered Social Innovation: Global Perspectives on an Emerging Paradigm’ draws upon ‘northern’ understandings of change and improvement as well as ‘southern’ theory concerns for epistemological diversity and meaning making. The result is an experiment aimed at reimagining research and practice that seriously needs to center the actor in processes of social transformation.
Keywords: Innovation sociale; Réservé UdeM; Transformations sociales